A new monitoring-while-drilling method of large diameter drilling in underground coal mine and their application. (March 2021) - Zhang, Wenlong; Li, Chen; Jin, Junxiao; Qu, Xiaocheng; Fan, Shuo; xin, Chongwei
Highlights: Microseismic system was used to monitor large diameter drilling hole construction. Measured vibration signals can express the depth of drilling hole. The method can reflect the regional stress concentration degree. The method can evaluate pressure relief effect of drilling hole. Abstract: Large Diameter Drilling (LDD) is a widely-used pressure relief method in underground coal mine, but LDD is now only used as a measure to reduce the occurrence probability of rock burst, the drilling difficulties and dynamic phenomena are not used efficiently. Innovative Monitoring-While-Drilling (MWD) technology is put forward by using microseismic (MS) system to monitor the vibration signals and excellent results have been achieved. MS monitoring results can display the actual depth of LDD holes and express the drilling difficulty of different depths to reflect stress state. Besides, measurement coal vibration events can reveal the degree of pressure relief. The experimental results are of great value to drilling depth supervision, abutment pressure distribution, and pressure relief effect evaluation.